Intraocular lens power calculation in eyes with short axial length - Moschos, Marilita M. (Medknow Publications & Media Pvt Ltd, 2014)
AIM: To evaluate and compare the predictive capacity of four intraocular lens (IOL) power calculation formulas (SRK/T, Hoffer Q, Holladay 1, and Haigis) in eyes shorter than 22.0 mm. SETTING AND DESIGN: Observational study. MATERIALS AND METHODS: Participants in our study were 69 consecutive patients with a preoperative axial length (AL) of less than 22.0 mm in one or both eyes. All patients underwent phacoemulsification with IOL implantation and postoperative target of refraction was analyzed. Specifically, the differences in the mean absolute estimation error (AE) for the four formulas were analyzed. Furthermore, the percentage of eyes with AE within ±0.5 and ±1.0 D for each formula was estimated, as well as the correlation coefficient (r) between the AL and estimation error (E) for each formula. The Mann-Whitney U test was used to compare differences in the AEs of the formulas. A statistically significant difference was defined as P < 0.05. RESULTS: The Haigis formula had statistically significant smaller mean AE in comparison to Holladay 1, Hoffer Q, and SRK/T. The Haigis formula predicted more eyes with E within ±0.5 and ±1.0 D of predicted spherical equivalent compared to other formulas. Correlation between AL and AE revealed a negative r value and P < 0.05 for all formulas. CONCLUSIONS: Haigis formula provides more accurate results concerning the postoperative target of refraction in eyes with AL less than 22.0 mm. Hoffer Q could be also used as an alternative.